Phenothiazinyl Boranes: A New Class of AIE Luminogens with Mega Stokes Shift, Mechanochromism, and Mechanoluminescence. Issue 29 (3rd May 2017) - Arivazhagan, C.; Maity, Arunava; Bakthavachalam, K.; Jana, Arijit; Panigrahi, Suraj Kumar; Suresh, Eringathodi; Das, Amitava; Ghosh, Sundargopal
Abstract: Phenothiazines with a dimesityl boron moiety, a new class of aminoboranes with B−N linkage, were synthesized. These aminoboranes exhibited interesting photophysical behavior including aggregation‐induced emission (AIE), mechanochromism (MC), mechanoluminescence (ML), and a mega Stokes shift (up to 312 nm in hexane). The solid‐state emission of the aminoboranes could be switched reversibly by grinding–fuming processes. Furthermore, the phenothiazine derivative with a bromo and an arylborane group at 3‐ and 7‐positions exhibited bright mechanoluminescence. Abstract : A new class of phenothiazinyl boranes that exhibit aggregation‐induced emission, mechanochromism, mechanoluminescence, and a mega Stokes shift, are synthesized. The solid‐state emission of the aminoboranes can be switched reversibly by grinding–fuming processes.